Pengeluaran Sektor Publik, Pertumbuhan Ekonomi dan Kemiskinan di Indonesia - Prasetyia, Ferry; Wulandari, Farah; Hutama, Ri Setia (Jurnal Ekonomi dan Pembangunan Indonesia, 2011)
The aim of this paper was to determine the effect of public sector expenditure to economic growth and poverty in all provinces in Indonesia during period 2006 to 2008. Using Full Information Maximum Likelihood (FIML) approach, the result showed that public sector expenditure on education and health sector had significant effect in boosting economic growth. Inaddition, the output produced by the education and health sector, both of the output had significant effect on economic growth. While, public sector expenditure on infrastructure had insignificant effect. Furthermore, this study showed that public sector expenditure on education and health also had significant effect in reducing the number of poor through the outcome such as form of school enrollment, literacy, infant mortality and life expectancy. On the other hand, the effect of economic growth to reduce the number of poor was not significant.